Identification and molecular characterization of 16SrV group phytoplasmas with flowering cherry in China. Issue 2 (14th March 2014) - Wang, L.‐P.; Hong, N.; Xu, W.‐X.; Wang, Y.‐F.; Chofong, G.‐N.; Martini, M.; Su, J.‐M.; Wang, G.‐P.; Woodward, S.
Summary Flowering cherry (Prunus serrulata) trees showing symptoms of excessive axillary growth, stunting, short internodes and decline were observed in Yantai City, Shandong province, China. The samples with the flowering cherry decline were designated as FcD‐YT phytoplasma. Sequencing results, restriction fragment length polymorphism (RFLP) and phylogenetic analysis of sequences from the 1248‐bp R16F2n⁄R16R2 products and partial ribosomal protein operon genes revealed the FcD‐YT phytoplasma as a member of subgroup 16SrV‐B, rpV‐C. Two RFLP patterns were observed in recombinant colonies from the cloned 16S rDNA gene with endonucleases HpaII and MseI. To our knowledge, this is the first report of 16SrV group phytoplasma declining flowering cherry trees in China.